Bridging STEM gaps in island education: Empowering teachers through contextual training in Indonesia - Marthinu, Eva; Pasongli, Hernita; Maryani, Enok; Ruhimat, Mamat; Waluya, Bagja; Saminan, Nurul Fajri (Education and Development Research, 2026)
This study investigates the impact of contextual STEM training designed for Subject Teacher Forum Subject Teacher Forum Geography teachers in Ternate, Indonesia, an island region facing geographical and educational challenges, where empirical evidence on localized and contextualized STEM professional development remains limited. The research employed a quantitative approach using a pre-experimental one-group pretest–posttest design with 20 participating teachers. Data were collected through a 20-item multiple-choice test validated by experts and analyzed using gain scores, inferential statistics, and effect size estimation. The results demonstrated a substantial improvement in teachers’ STEM knowledge, with the mean pretest score increasing from 8.90 to 13.20 (N-Gain = 0.59, moderate-to-high). Inferential analysis confirmed a significant improvement (p < 0.001) with a very large effect size (Cohen’s d = 2.44). Interestingly, teachers from non-education backgrounds achieved slightly higher learning gains compared to education majors, suggesting that contextual STEM concepts can be effectively acquired regardless of prior specialization. The findings confirm that short-term, localized, and context-based training is effective in enhancing teachers’ pedagogical knowledge, reducing initial disparities, and empowering educators to design relevant STEM-based geography learning. This model contributes to the growing body of research on STEM professional development, advances geography education through context-based pedagogy, and offers a replicable framework for teacher capacity building in island and under-resourced regions.